Organophosphorus‐Catalyzed Deoxygenation of Sulfonyl Chlorides: Electrophilic (Fluoroalkyl)sulfenylation by PIII/PV=O Redox Cycling. (25th January 2019) - Ghosh, Avipsa; Lecomte, Morgan; Kim‐Lee, Shin‐Ho; Radosevich, Alexander T.
Abstract: A method for electrophilic sulfenylation by organophosphorus‐catalyzed deoxygenative O‐atom transfer from sulfonyl chlorides is reported. This C−S bond‐forming reaction is catalyzed by a readily available small‐ring phosphine (phosphetane) in conjunction with a hydrosilane terminal reductant to afford a general entry to sulfenyl electrophiles, including valuable trifluoromethyl, perfluoroalkyl, and heteroaryl derivatives that are otherwise difficult to access. Mechanistic investigations indicate that the twofold deoxygenation of the sulfonyl substrate proceeds by the intervention of an off‐cycle resting state thiophosphonium ion. The catalytic method represents an operationally simple protocol using a stable phosphine oxide as a precatalyst and exhibits broad functional‐group tolerance. Abstract : Sauerstoffe auf Wanderschaft : Ein Verfahren zur elektrophilen Sulfenylierung beruht auf einem Organophosphor‐katalysierten desoxygenierenden O‐Atom‐Transfer (OAT) aus Sulfonylchloriden. Diese C‐S‐Kupplung wird durch das Phosphetan 1 in Verbindung mit einem Hydrosilan als terminalem Reduktionsmittel katalysiert und liefert wertvolle Sulfenyl‐Elektrophile, darunter Trifluormethyl‐, Perfluoralkyl‐ und Heteroarylderivate.